Changes in Echocardiographic profile of NSTEMI patients, before and after PCI in Diabetes vs. Non-Diabetes group - Anwar, AFM Azim; Mumu, Sanjida Anjum; Ali, Md Yousuf; Tirtho, Srizon Roy; Siddik, Adib; Chowdhury, MSI Tipu; Khaled, Md Fakhrul Islam; Saklayen, SMG; Hoque, Harisul (University Heart Journal, 2024)
Background: Revascularization may improve outcomes of patients with LV dysfunction by improvement of EF. Though this is not so, in diabetic patients. Because diabetic ischemic etiology is consistently reported as a risk factor for lack of ejection fraction (EF) improvement after revascularization. The determinants of EF improvement havenot yet been investigated comprehensively among diabetic vs nondiabetic group. The goal of the study was to examine how diabetic and non-diabetic patients’ left ventricular systolic performance change from the beginning of the trial to three months following PCI. Methodology: This comparative clinical study, conducted at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from January to December 2018 with IRB clearance (Protocol No: BSMMU/2017/ 6624), adhered to Helsinki declaration principles. Patient selection based on inclusion/exclusion criteria involved comprehensive history-taking and clinical examinations. Transthoracic 2D echocardiography was performed pre-PCI, at discharge, and 3 months post-PCI using validated measurements. Left ventricular function parameters were assessed, and coronary angiography preceded percutaneous coronary intervention (PCI) with newer drug-eluting stents. Standard procedural techniques and anticoagulation were employed, maintaining medication consistency to minimize confounding variables. Results: In our study, diabetic patients significantly improved systolic function, after PCI, to the point where it was nearly comparable to non-diabetes. Most of these measures were poorer in diabetics than in nondiabetics at baseline. However, in this subgroup, our study also demonstrated excellent reversibility of these negative effects following PCI. After PCI, there was also a change in LVEF in non-diabetics. Both people with diabetes and people without diabetes showed improvement in WMA. However, the degree of improvement in these two groups varied. Discussion: This study compared coronary stenosis in diabetic and non-diabetic patients. Diabetics exhibited significantly higher LAD stenosis (60% vs. 40%), while RCA and LCx stenoses were similar. Baseline LVEF, LVESV, and LVIDs showed no significant differences between groups. Diabetics had more regional wall motion abnormalities. Three months post-PCI, both groups improved in LV parameters, with no significant inter-group differences. Diabetic patients showed improved LVEF, contrary to a study by Nabati et al. in non-diabetics. Regional wall motion abnormalities decreased more in non-diabetic patients Conclusion: Contrary to the common belief favoring CABG for diabetics, our study indicates that newer drug-eluting stents offer comparable benefits in clinical outcomes, survival rates, and LV systolic function improvements for both diabetic and non-diabetic patients. University Heart Journal 2023; 19(2): 45-48